SisKeuDes dan Tata Kelola Keuangan Desa: Kajian Literatur mengenai Transparansi dan Akuntabilitas - Pratiwi, Yanna Eka (JFAS : Journal of Finance and Accounting Studies, 2026)
This study examines the role of village financial management systems in strengthening transparency and accountability in the administration of Dana Desa. Using a systematic literature review, the article synthesizes findings from academic journals, government regulations, and institutional reports to analyze how village governance practices, accounting standards, and digital systems interact in shaping the quality of financial accountability. The results show that although regulatory frameworks such as Permendagri No. 20/2018, SAPDesa, and the SiskeuDes application have been widely implemented, their effectiveness remains limited due to varying levels of technical capacity among village officials, inadequate documentation practices, and infrastructure disparities. Transparency tends to be symbolic, while accountability is often administrative rather than substantive. Community participation is also constrained by limited access to information and low literacy in public budgeting. The study concludes that improving village financial governance requires capacity building, simplified administrative procedures, sustained technical assistance, and broader public engagement to support responsive and accountable local governance.